Social participation and inclusion of ex-combatants with disabilities in Colombia (2019)
The purpose of this paper is to explore ex-combatants’ understandings of disability and the pathways for social reintegration available to them in Colombia. The qualitative data for the study include seven in-depth interviews with ex-combatants and 29 with key informants, including disabled people’s organisations, government agencies, international organisations and academic groups. Findings suggest that transition to civilian life for ex-combatants is made more difficult by inadequate procedures, lack of support and complex administrative data vacuums. Social determinants, historical prejudice against persons with disabilities, high levels of unemployment and political polarisation in a post conflict context combine to trigger poverty traps. The findings indicate pitfalls in the early implementation of the Colombian peace process, which did not consider structural issues that affected transition to civilian life for ex-combatants with disabilities. Furthermore, key enablers for social inclusion such as peer-to-peer support have been identified by respondents.